Anísio Teixeira - Agueda Bittencourt (Cahiers de la Recherche sur l'Education et les Savoirs)
The social and intellectual trajectory taken by educator Anísio Teixeira are studied in this article, considering his geographical backgrounds in Bahia, a politically peripherical state compared to the southern and southeastern states of Brazil, as well as his social backgrounds, which did not indicate the important role he would play in an international scope, much before the age of 40. Several documents with records of his international trips allow an analysis of vital moments when he collected the first pieces of information on education and the way he explored his contacts with intellectuals and politicians in modern institutions in Europe and the United States, aiming to develop the sketch for an educational project for Brazil at a time of political change, that is, the period from 1925 to 1934.